Patterns legitimizing political violence in transcultural perspectives : Islamic and Christian traditions and legacies - Koch, Bettina, 1970- (Judaism, Christianity, and Islam - tension, transmission, transformation ;, 2015)
This volume analyzes discourses in which religion is used to legitimize political violence. The research centers on both premodern and modern Islam and Christianity outside the post-industrial world, with a particular focus on the Middle East and Latin America, thus filling a gap in the existing literature. The resulting study and its contribution to conflict resolution is relevant for academics and political practitioners alike.